The quest of Ewilan. Book two, Akiro - Lylian, 1975- (Euro Comics, 2019)
Now in Gwendalavir with her friend Salim, Ewilan hones her ability to imaginate in order to help her people gain the power to win the war. When things become even more dangerous, she embarks on a quest to find her brother for help.